Pemanfaatan Deep Learning terhadap Hasil Belajar Siswa dalam Pembelajaran IPS di SD - Aufa Salsabila; Azmi Hafidzoh; Adrias Adrias (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Educational developments in the digital era demand teaching methods that foster critical thinking, literacy, and active student engagement. However, social studies instruction in elementary schools still largely relies on conventional, rote-memorization-based methods, resulting in suboptimal student understanding. This study aims to analyze the application of deep learning in social studies instruction in elementary schools, covering implementation strategies, impacts on learning outcomes, as well as supporting factors and challenges. The method used is a literature review analyzing national scientific articles from the past five years via Google Scholar using relevant keywords. The findings indicate that deep learning can improve learning outcomes, conceptual understanding, student engagement, and critical thinking skills. Commonly used strategies include contextual learning, integration of local wisdom, innovative media, and collaborative discussions based on social issues. The main obstacles to implementation include teacher readiness, limited media resources, and insufficient learning time. Therefore, it is necessary to improve teacher competencies as well as provide support for media and learning systems to ensure the optimal implementation of deep learning.